Atypical phenotypic aspects of autoimmune thyroid disorders in young patients with Turner syndrome - Tommaso Aversa; Romina Gallizzi; Giuseppina Salzano; Giuseppina Zirilli; Filippo De Luca; Mariella Valenzise (BMC, 2018)
Abstract Aim of this commentary is to analyze the current views about the phenotypic features of Hashimoto's thyroiditis (HT) and Graves' disease (GD) in Turner syndrome (TS) girls, in terms of epidemiology, clinical and biochemical presentation, long-term course and metamorphic autoimmunity evolution. In TS GD course is not atypical, whereas HT course is characterized by both a mild presenting picture and a severe long-term evolution of thyroid function tests. Furthermore, TS girls seem to have an increased risk of switching over time from HT to GD. On the light of these findings, it may be concluded that TS girls with HT need a careful monitoring of thyroid status over time. Conclusions: 1) In children the association with TS is able to condition a peculiar phenotypic expression of HT in terms of epidemiology, presentation course and long-term metamorphic autoimmunity; 2) by contrast, children with TS do not exhibit an atypical clinical and biochemical course of GD, but only a significantly higher prevalence of this disease.